Integrative taxonomists should use and produce DNA barcodes - Padial, José M.; de La Riva, Ignacio (Zootaxa, 2007)
Put simply, DNA barcoding (DNAB) is an identification method that aims to relate short, specific DNA fragments from unidentified specimens to sequences of previously identified voucher specimens through comparison of sequence divergence (Hebert et al. 2003). DNAB has produced noticeable success in terms of scientific citation and media coverage because it is technically feasible, commercially attractive, and philosophically acceptable to many scientists (Smith 2005). Irrespective of the utility to the general public (Cameron et al. 2006), and contrary to other DNA-based methods with taxonomic purposes (Vogler & Monaghan 2006), identification through DNAB is becoming widely available (www.barcodinglife.org). While DNAB is rejected by some taxonomists who view it as a competitor for funds, or a danger to taxonomy (Will & Rubinoff 2004; Ebach & Holdrege 2005), we argue for the complete incorporation of DNAB into integrative taxonomy (sensu Will et al. 2005).